The interplay of cultural identity and behavioral factors in promoting sustainable heritage tourism: A study on Islamic Mamluk heritage - Abdelghani, Abdelrahman Ahmed Abdelhai; Ammar, Salama Ammar Mohammed; Ahmed, Hebatallah Ahmed Mokhtar Taha (Research Journal in Advanced Humanities, 2025)
This study investigates the interplay between cultural identity and behavioral factors in promoting sustainable heritage tourism, focusing on Egypt’s Islamic Mamluk heritage (1250–1517 CE). Utilizing a mixed-methods approach, a structured questionnaire was administered to 215 visitors to analyze how cultural identity, behavioral intentions (guided by the Theory of Planned Behavior), and perceptions of heritage value influence sustainable tourism practices. Hypotheses tested revealed significant positive correlations: cultural identity strongly predicted sustainable tourism engagement (r = 0.697, p < 0.01), behavioral factors (attitudes, norms, perceived control) significantly influenced intentions (r = 0.628, p < 0.01), and Islamic cultural heritage value explained 62.5% of variance in sustainable tourism intentions (R² = 0.625). Regression analysis confirmed heritage value as a critical motivator (β = 0.791). Demographic variables (gender, education) showed no statistically significant moderating effects, suggesting universal applicability of strategies. Findings emphasize that preserving Mamluk heritage—architecturally and narratively—enhances visitor loyalty, community identity, and economic resilience. The study advocates for inclusive policies balancing commercialization with authenticity, leveraging digital tools and stakeholder collaboration. Results contribute to theoretical frameworks linking cultural identity, behavioral economics, and heritage sustainability, offering actionable insights for policymakers and heritage managers to foster ethical tourism aligned with cultural preservation and local empowerment.